2019
DOI: 10.1016/j.buildenv.2018.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Moisture in clothing and its transient influence on human thermal responses through clothing microenvironment in cold environments in winter

Abstract: Air humidity produces conditions of varying moisture contents in clothing, which affects the heat and moisture transfer between human body, clothing and environment, as well as the wearers' comfort. This study was designed to evaluate the moisture effects in clothing in cold environments. A series of wearing experiments were conducted in a climate chamber, simulating transient moisture absorption and desorption in experimental clothes. Totally 20 subjects were involved in three temperature levels (16 o C/20 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Therefore, more attention should be paid to high-temperature environments of nucleic acid sampling personnel, and it is necessary to study and analyze the thermal comfort of sampling personnel. suffer other effects after being covered [6,7], which can seriously affect their working efficiency and their health and increase the risk of heat stress [8][9][10][11]. Therefore, more attention should be paid to high-temperature environments of nucleic acid sampling personnel, and it is necessary to study and analyze the thermal comfort of sampling personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more attention should be paid to high-temperature environments of nucleic acid sampling personnel, and it is necessary to study and analyze the thermal comfort of sampling personnel. suffer other effects after being covered [6,7], which can seriously affect their working efficiency and their health and increase the risk of heat stress [8][9][10][11]. Therefore, more attention should be paid to high-temperature environments of nucleic acid sampling personnel, and it is necessary to study and analyze the thermal comfort of sampling personnel.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is drawn mainly according to the finding in our previous study [67] that the relative humidity has no significant effect on the skin temperature 30 in the range of 15%-85% in most winter conditions. The reasons for that could be the opposite effect of the increased (or decreased) vapor pressure in air and the increased (or decreased) moisture in heavy clothing on body surface heat transfer at the same time [68].…”
Section: Discussion Of the Difference In Other Conditionsmentioning
confidence: 99%
“…2527 Du et al. 28 also showed that the effect of water content on human mean skin temperature was significant ( p < 0.05) in a cold-humidity climate ( T a 16–24°C, relative humidity (RH) 15–85%). These studies indicate the great necessity of improving the accuracy of the physical properties considering moisture in thermal response prediction models.…”
mentioning
confidence: 97%
“…Takanokura et al 24 have demonstrated that the moisture inside clothing can cause a variation of 0.3 units in the predicted vote for thermal sensation. [25][26][27] Du et al 28 also showed that the effect of water content on human mean skin temperature was significant (p < 0.05) in a cold-humidity climate (T a 16-24 C, relative humidity (RH) 15-85%). These studies indicate the great necessity of improving the accuracy of the physical properties considering moisture in thermal response prediction models.…”
mentioning
confidence: 99%